Enhanced activity localization and microscale dosimetry in alpha-emitter radiopharmaceutical therapy using integrated autoradiography and histological imaging - Sandeep Sahota; Krystal A. Quirindongo; Joseph Piccolo; Anupriya Chhabra; Nouran Zaid; Simin Deveauxbray; Kenechukwu C. Charles-Obi; Brian Miller; Robert F. Hobbs; George Sgouros; Remco Bastiaannet (Scientific Reports)
Abstract Alpha-emitter radiopharmaceutical therapy delivers highly localized radiation, offering potent therapeutic effects. However, microscale heterogeneity remains poorly characterized in vivo and may affect efficacy. This underscores the critical need for sub-organ dosimetry to better understand αRPT radiobiology and guide treatment optimization. While autoradiography enables high-resolution activity mapping, conventional approaches lack anatomical context for accurate dose mapping. To address this, we propose a comprehensive workflow integrating quantitative autoradiography with histological imaging. Tissues from αRPT-treated mice bearing HER2 + breast tumors were snap-frozen, sectioned, and imaged using autoradiography. The same sections were histologically stained and used for precise autoradiography-histology integration. These anatomical contexts were then used to accurately stack multiple sections in a 3D volume, and were used for subsequent microscale dosimetry. Both tumor and kidney tissues were analyzed. Snap-freezing in isopentane preserved tissue morphology optimally. Our method enabled precise activity localization, revealing significant accumulation in the kidney cortex region close to glomeruli. Anatomical context improved 3D reconstructions needed for accurate dose estimations in tumor tissue. This methodology enhances αRPT dosimetry by precise spatial mapping of autoradiography unto the underlying tissue morphology. These advancements provide crucial insights into αRPT spatial radiobiology at the near-cellular level and will aid in optimizing radiopharmaceutical design and treatment planning.